Elements for a social history of american social sciences: A chronicle - Ione Ribeiro Valle; Tiago Ribeiro Santos (Tópicos Educacionais)
This interview with Erving Goffman (1922-1982) was conducted in 1980 by French researcher Yves Winkin. Complying with Goffman's demands, Winkin conducted this interview without using tape recorders, relying mainly on the notes taken during the meeting. Winkin presents elements of Goffman's intellectual itinerary, such as the professors who marked his formation, the problems related to academic recognition in the American university field, and his challenges against the symbolic interactionist label.